PENGUATAN KINERJA PEGAWAI KANTOR KESYAHBANDARAN DAN OTORITAS PELABUHAN KELAS I TANJUNG EMAS SEMARANG - Rauly Sijabat; Ignatius Martanto (JURNAL SAINS DAN TEKNOLOGI MARITIM, 2023)
The study of employee performance is not a new study. Nevertheless, research on performance is still relevant to be studied, especially those explained by workload and work stress factors. Workload and work stress are classic phenomena that many employees experience in the workplace. In addition, from the results of previous studies, the influence described on performance also shows results that are not yet conclusive. This finding prompted a study to determine the effect of workload and work stress on employees at the Class I Port Authority and Port Authority Office of Tanjung Mas Semarang. Data related to workload, work stress and performance were obtained through interviews using a questionnaire for further analysis using the Structural Equation Modeling (SEM) approach. From the results of statistical analysis shows that the workload is statistically proven to cause work stress. The results of this study also show that exposure to workload and work stress experienced by employees continuously will cause a decrease in employee performance.